Will Mangrove Reforestation Provide Net Benefits: A Case in Sibunag, Guimaras - Fernandez, Cheryl Joy; Subade, Rodelio; Parreño, Paul Erwen (Science Diliman: A Journal of Pure and Applied Sciences, 2007)
In response to the threats in mangrove resources such as massive fishpond conversion, industrialization, and increased human settlements in coastal areas, the province of Guimaras answered these threats by widespread mangrove reforestation projects in its coastal communities. These projects were found out to be beneficial, as depicted on large gap on the mangroves overall benefits and the costs of implementation of the mangrove reforestation project. Results of the study show that the present total benefit of mangrove per hectare with sustainable harvesting in the first year is lesser than the costs. However after the first year, the net benefits are positive. However, in compliance with Republic Act 7161 (R.A. 7161) that banned the cutting/using of all mangrove species, cost-benefit analysis of mangrove reforestation without harvesting was also computed. The net benefits exceed the costs from the start of the year up to the 20th year. Both the scenarios include the Mean WTP equivalent to PhP 142.75, which is the amount people are willing to give for the conservation of mangroves. The net present values (net benefits) of mangrove reforestation were found positive for both scenarios: with sustainable harvesting and without harvesting.